2021
DOI: 10.1021/acs.iecr.0c06193
|View full text |Cite
|
Sign up to set email alerts
|

Dissipative Particle Dynamics Quantitative Simulation of the Formation Mechanism and Emulsification Driving Force of Deep Eutectic Solvent-Based Surfactant-Free and Water-Free Microemulsion

Abstract: The reason for the formation of an anhydrous and surfactant-free deep eutectic solvent (DES)-based microemulsion system has been widely explored so far. Dissipative dynamism (DPD) is used to simulate the composition of DES, diethyl adipate (Da), and tetrahydrofurfuryl alcohol (THFA) systems to study their emulsification mechanism and quantitative properties. The influence of the proportions of different DES, Da, and THFA components on the phase formation of microemulsion was discussed through simulations. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The simulation results made it possible to describe the structure of the hierarchical porous structure of ZIF-8 and the mechanism of its formation. Fan et al [ 179 ] used DPD to study microemulsions based on DES (ChCl/urea), tetrahydrofurfuryl alcohol (THFA), and diethyl adipate (DA). The simulations were used to calculate the phase diagram, which was found to be in good agreement with experimental data.…”
Section: Simulation Methods For Dessmentioning
confidence: 99%
“…The simulation results made it possible to describe the structure of the hierarchical porous structure of ZIF-8 and the mechanism of its formation. Fan et al [ 179 ] used DPD to study microemulsions based on DES (ChCl/urea), tetrahydrofurfuryl alcohol (THFA), and diethyl adipate (DA). The simulations were used to calculate the phase diagram, which was found to be in good agreement with experimental data.…”
Section: Simulation Methods For Dessmentioning
confidence: 99%
“…The simulation results made it possible to describe the structure of the hierarchical porous structure of ZIF-8 and the mechanism of its formation. Fan et al [163] used DPD to study microemulsions based on DES (ChCl / urea), tetrahydrofurfuryl alcohol (THFA), and diethyl adipate (DA). The simulations were used to calculate the phase diagram, which was found to be in good agreement with experimental data.…”
Section: Coarse-grained Modelsmentioning
confidence: 99%
“…More recently, Wang and co-workers proposed that the partitioning of amaranth was precisely controlled by an addition of DES as the phase adjuvant of ABS, but the concrete phase composition was not studied in their work. Our previous work revealed that menthol-based DES showed high efficiency to extract triphenylmethane dyes from aqueous solution, indicating the biocompatibility and potency of DES compared with those of organic solvents. However, there were still large amounts of gaps in the recycling and reusability of DES for the DES-based ABS. In addition, it must be highlighted that the determination of phase diagrams and tie-lines composition was of great importance for predicting the distribution equilibrium of DES-based ABS.…”
Section: Introductionmentioning
confidence: 99%